Épica y bildungsroman en La Dionisiada de Salomón de la Selva: El héroe positivo y la revolución - Chen Sham, Jorge (2017)
Within this epic conception believing that wars and insurrections test the making of a hero, his positive education is expressed through his preparation for thought and action. This article tries to analyze how Salomón de la Selva proposes, in La Dionisiada, that a revolution needs a great leader in order to boost itself. In Nicaragua, during the XIX and XX centuries, revolution depends on the leader’s values that shape a national identity; such is the case of General Dionisio. The author wields reasons to recognize the figure of Augusto César Sandino in General Dionisio.